Adjustments That Enhance Academic Performance of Learners with Physical Impairments in Public Primary Special Schools in Nyanza Region, Kenya - Nyangoya, Eunice Adhiambo (JOOUST, 2023)
Physical Impairment (PI) impacts on learning in that a pupil with PI may have difficulties with; managing the distance between different learning activities, carryi ng materials, note taking, practicals, and may also take longer to ask or answer questions. Without appropriate adjustments, these may negatively affect their academic performance. Pupils with PI in most public primary special schools in Nyanza Region have been performing dismally academically. The purpose of the study was to explore the adjustments that enhance academic performance of learners with PI in public primary special schools in Nyanza Region, Kenya. The research objectives were, to: determine the relationship between adaptation of physical facilities and academic performance of pupils; establish the relationship between access to counseling services and academic performance of learners; find out the relationship between access to physiotherapy (PT) services and academic performance of learners; and, to determine the relationship between access to occupational therapy (OT) services and academic performance of learners with PI. The research was guided by Social Model of Disability theory; it used mixed-methods approaches and concurrent triangulation design. The target population was 1433 participants, that is; 6 head teachers, 92 teachers, 6 school counselors, 6 PTs, 6 OTs, and 1317 pupils. Simple random sampling technique, saturation sampling, and purposive sampling technique were used to select; 396 pupils; 6 head teachers, 6 counselors, 6 PTs, and 6 OTs; and 48 teachers respectively, a total of 468 respondents. Data was collected using questionnaire for pupils, interview schedules, Focus Group Discussions, and an observation checklist. Content validity and Cronbach’s alpha were used for validity and reliability respectively. Quantitative data was analyzed using descriptive and inferential statistics, and thematic analysis for qualitative data; from which conclusions were made. The research findings indicated that: there was inadequate adjustments that enhance academic performance of learners with PI in public primary special schools; there was; a statistically significant positive relationship (r= .370) between adaptation of physical facilities and academic performance,; a statistically significant positive relationship (r= .271) between access to counseling services and academic performance; a statistically significant positive relationship (r= .448) between access to PT services and academic performance; and a statistically significant positive relationship (r= .604) between access to OT services and academic performance. It was concluded that the 4 aspects of adjustments are inadequate, and their inadequacy contributes to poor academic performance of pupils in public primary special schools in Nyanza Region. The research findings recommended that there is need for the Ministry of Education and other stakeholders to facilitate; adequate provision of adapted physical facilities, access to counseling services, access to PT services, and access to OT services in public primary special schools for learners with physical impairments
Keywords: Physical Impairments